Rhodobacterales and Rhizobiales Are Associated With Stony Coral Tissue Loss Disease and Its Suspected Sources of Transmission - Rosales, Stephanie M.; Clark, Abigail S.; Huebner, Lindsay K.; Ruzicka, Rob R.; Muller, Erinn M. (Frontiers in Microbiology, 2020)
In 2014, Stony Coral Tissue Loss Disease (SCTLD) was detected off the coast of Miami, Florida, USA, and continues to persist. Along the Florida Reef Tract (FRT), coral reefs have previously succumbed to disease outbreaks. However, SCTLD can have up to a 99% mortality rate and has affected 23 species of scleractinian corals. In addition to its high mortality rate, its fast spread through the FRT has led to the regional near-extinction of at least one coral species, Dendrogya cylindrus. Although the disease has persisted for over 5 years, the etiology of SCTLD is unknown. As a means to characterize potential SCTLD pathogens, we collected tissue samples from four affected coral species: Stephanocoenia intersepta, Diploria labyrinthiformis, Dichocoenia stokesii, and Meandrina meandrites. Tissue samples were from apparently healthy (AH) corals, and unaffected tissue (DU) and lesion tissue (DL) on diseased corals. Samples were collected from three zones: (1) Lower Florida Keys (ahead of the SCTLD disease boundary, “vulnerable zone”), (2) Upper Florida Keys (post-SCTLD outbreak, “endemic zone”), and (3) Middle Florida Keys (SCTLD was active and prevalent, “epidemic zone”). From each zone, sediment and water samples were also collected to identify potential reservoirs of the SCTLD pathogen. We used 16S rRNA gene amplicon high-throughput sequencing methods to characterize the microbiomes of the coral, water, and sediment samples. We identified a relatively higher abundance of the bacteria orders Rhodobacterales and Rhizobiales in DL compared to AH and DU tissue. Also, our results showed relatively higher abundances of Rhodobacterales in water from the endemic and epidemic zones compared to the vulnerable zone. However, potential Rhodobacterales and Rhizobiales pathogens identified from DL were detected in sediment samples, but not in water samples. Our data indicate that Rhodobacterales and Rhizobiales may play a role in SCTLD and that sediment may be a disease reservoir.